Evaluation of a cost-effective and energy-efficient disc material for rotating biological contactors (RBC), and performance evaluation under varying condition of RPM and submergence. Issue 43 (13th September 2016) - Tabraiz, Shamas; Haydar, Sajjad; Hussain, Ghulam
Abstract: This study was carried out to evaluate the suitability of polyethylene foam as disc material for rotating biological contactors (RBC). Effect on DO levels due to change in RPM and submergence was also investigated. For this purpose, a pilot-scale model of RBC was constructed. The model was operated at 3, 5 and 7 RPM with varying submergence of discs, i.e. 30, 40, 50, 60 and 70%. Domestic sewage was used to run the model. Different parameters like pH, DO, total suspended solids (TSS), BOD and COD were monitored for the influent and effluent of pilot-scale RBC under varying operating conditions. Optimum values of submergence and RPM were found to be 40% and 5 RPM, respectively. BOD and COD removal, under optimum conditions, were 85.7 and 67.6%, respectively. The effluent concentrations for BOD and COD, under optimum conditions, were 42 and 124 mg/L, respectively, meeting the national effluent standards, with DO level of 4.6 mg/L. New disc material used costs US$ 0.38, while conventionally used material, i.e. polystyrene costs US$ 1.91 per square metre. Due to lesser weight energy consumption of newly proposed material is 26 kWh/m 3 /year while for Polystyrene it is 96.6 kWh/m 3 /year, no wear and tear of material was found after a continuous run of 90 d. Analysis of variance showed that submergence has more dominant role in raising DO levels as compared to RPM.